Valores humanos e bullying: um estudo pautado na congruência entre pais e filhos - Soares, Ana Karla Silva (2013)
This work aimed to determine the influence of parents on their children evaluative priorities and its relationship to bullying behavior. Sought to gather evidence of the validity and accuracy of the measurements used in the study, the correlates of bullying and evaluative predictive power of human values in the face of this construct. Participants were 1.007 people from João Pessoa (PB), and 623 students, ages 9 to 16, the majority of public schools (68.5%), catholic (59.4%) and females (52.9% .) 384 parents / guardians, aged 18 to 70 years, the most of them female (78.8%) and catholic (64.8%). After treatment of the remaining 351 data pairs (parent - child) of participants. The children responded to Positive Attitude Scale Facing Potential Targets of Bullying (PASFPTB), Scale California Bullying Victimization (ECBV), Parental Perception Questionnaire (PPQ), the Basic Values Questionnaire (BVQ or BVQ-C) and sociodemographic questions. While parents or guardians received booklet containing the PASFPTB, Scenarios Bullying in School Context and BVQ. The results show the validity and accuracy of measurements of human values (BVQ), bullying, which proved the structure of one factorial PASFPTB, which explained 31% of the total variance, with factor loadings between 0.40 and 0.65 and internal consistency (Cronbach's alpha) of 0.91, and ECBV, which also showed a one-factor structure, explaining 42.4% of the total variance, with Cronbach's alpha of 0.75 and factor loadings ranging from 0.58 to 0.75 , and also proven structures of the scales of parenting styles (PPQ). Then, with the aim of knowing the correlates of bullying evaluative seven hypotheses were formulated. The first three were confirmed, indicating that children evaluative priorities are congruent with those of their parents, with the dimension of authoritative parenting style directly related to the personal values of father and mother, and that the relationship between the perceived values by the parents and children prioritized the children are moderated by the size affective dimension of father and mother, specifically, the personal values of the mother and the core personal and parental. Hypotheses four, five and six were also confirmed, since the scores of parents and children in positive attitudes to potential bullying targets are directly related (r = 0.44) and the scores of the children in bullying target are positively correlated with personal values (r = 0.10) and negatively with the social (r = -0.12). Finally, is the seventh confirmed case in which the values of the children [social (β = 0.23, t = 3.51, p < 0.001) and personal (β = -0.30, t = -4.13, p <0.001)] were predictors of bullying. In conclusion, trusts that the objectives proposed in this thesis have been achieved, contributing to the field of study that relates the congruence of values of parents and children with bullying behavior. However, it recognizes the need for new studies focusing on the transmission of values, intervention techniques and employment of a child under age shows.